The Role Of Organizational Competence And Commitment On Employee Performance With Innovation Behavior As An Intervening Variable: Study at the Pemalang Regency Fisheries Service - Sri Mertiningsih; Legiman Legiman; Syamsul Haris (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to identify the role of employee competence and organizational commitment on employee performance, with innovative behavior as an intervening variable. Due to the population being less than 100 respondents, the study uses a census technique, taking all 50 employees of the Fisheries and Marine Office as the sample. Path analysis is employed as the data analysis technique. The results show that competence has a positive and significant effect on employee performance, organizational commitment also has a positive and significant effect on employee performance. Furthermore, competence has a positive and significant effect on innovative behavior, and organizational commitment similarly has a positive and significant effect on innovative behavior. Innovative behavior itself has a positive and significant effect on employee performance. It is also found that innovative behavior can mediate the competency variable on employee performance, and innovative behavior can also mediate the organizational commitment variable on employee performance.